Case report: Epidermolysis bullosa acquisita following dipeptidyl peptidase-4 inhibitor therapy and complicated by immune thrombocytopenic purpura - Kawamoto, Hirofumi; Sasaki, Natsuko; Ueda, Yukimi; Ishii, Norito; Sawada, Yu (Frontiers in Immunology, 2026)
Epidermolysis bullosa acquisita (EBA) is a rare autoimmune blistering disease caused by autoantibodies to type VII collagen. While dipeptidyl peptidase-4 (DPP-4) inhibitors are established triggers for bullous pemphigoid (BP), their association with EBA has not been reported. A 68-year-old Japanese man with type 2 diabetes and chronic renal dysfunction, treated with linagliptin, developed widespread tense blisters with mucosal involvement. Histopathology and immunological studies confirmed EBA. Despite corticosteroids, cyclosporine, pulse therapy, and intravenous immunoglobulin, the disease remained refractory. Eighty days after onset, he developed pneumonia, renal failure requiring dialysis, and severe thrombocytopenia. After exclusion of other causes, immune thrombocytopenic purpura (ITP) was clinically diagnosed. Although treatment yielded transient platelet recovery, the patient ultimately died. This is the first reported case of EBA following DPP-4 inhibitor therapy complicated by ITP. It highlights the therapeutic challenges of EBA and the potential for systemic autoimmune manifestations beyond the skin in patients receiving DPP-4 inhibitors.